Strategy-Proof Allocation Mechanisms at Differentiable Points - Satterthwaite, Mark A.; Sonnenschein, Hugo (Review of Economic Studies, 1981)
Mark A. Satterthwaite, Hugo Sonnenschein; Strategy-Proof Allocation Mechanisms at Differentiable Points, The Review of Economic Studies, Volume 48, Issue 4